Correção das atitudes desviantes da mineração na busca da sustentabilidade jurídica da exploração de bens ambientais - Martins, Emilio Ornelas (2021)
The theme of this monographic work is Correction of Deviating Attitudes of Mining in the Search for Juridical Sustainability in the Exploration of Environmental Goods and it is focused on how the State, intervening by punishing attitudes deviating from the law, can guide the performance of companies that operate in the field of mining for the functionalization of law, within the notion of juridical sustainability. Bearing in mind that all economic activities produce some type of degradation, this work uses the term juridical sustainability understood as the one in which the activity takes place according to the state regulation established for the environmental protection of the sector, and this concept is also part of the hypothesis of research. The general objective is to study the legal aspects of the liability of mining companies, for conduct deviating from the law within the notion of sustainability. In order to achieve this objective, aspects of mining law were studied, especially the obligations imposed by mining concession titles, with their environmental components, and also the requirements brought by environmental laws for mining enterprises were studied. Once the legal requirements for mining were known, starting from the Federal Constitution, it was analyzed how the State punished deviant conduct, forcing companies to follow juridical sustainability. The method used is that of doctrinal bibliographic research, jurisprudence and analysis of the relevant legislation. The juridical notion of sustainability of mining goes beyond environmental legislation, and deviating attitudes should be considered as those that are potentially or effectively harmful to the environment and contrary to the legal norms of the environmental mineral good and the punishment for such deviations depends on the severity of the fact. and can occur in the criminal, administrative and proven civil liability fields.